Turnover Intention and Work-life Balance as Predictors of Employee Performance Satisfaction at Springhill Group - Triana, Harry (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aimed to examine the influence of turnover intention and work-life balance on employee performance satisfaction at Springhill Group. The main issue addressed in this research was the increasing tendency of employees to consider leaving their jobs, which may negatively affect overall productivity and performance quality. In addition, the balance between work and personal life was also considered a critical factor contributing to employee satisfaction. A quantitative approach was used through a survey method, involving 50 respondents who were active employees from various divisions within the company. Data were analyzed using multiple linear regression. The results revealed that both turnover intention and work-life balance had significant effects on employee performance satisfaction. These findings highlight the importance of human resource strategies focused on minimizing turnover tendencies and promoting policies that support employees’ work-life balance to enhance overall job satisfaction and performance.